Bisnis Foto Prewedding: Komersialisasi Ritual Perkawinan pada Masyarakat Bali - Atmadja, Anantawikrama Tungga; Maryati, Tuty; Bawa Atmadja, Nengah (Jurnal Kajian Bali (Journal of Bali Studies), 2019)
This article is a part of the fundamental research result conducted for in 2019. The method is a qualitative research that refers to a critical paradigm. The research location is in various regencies in Bali. The results showed the use of prewedding in marriage ritual in Bali is triggered  by various reasons, namely not contrary to Hinduism, shame, the push of meme, postmodern identity, and the desire to show the status. The practice of prewedding is done by buying at prewedding entrepreneurs. This led to the perception of the commercialization of marriage in Balinese society. Commercialization is done in a variety of ways, namely to make prewedding as the creative industry, to develop a collaborative, create tiered quality prewedding, and conduct business activities with B2C model. Key words: Social change, prewedding, marriage, and commercialization